Prenatal inflammation impairs early CD11c-positive microglia induction and delays myelination in neurodevelopmental disorders - Kazuya Fuma; Yukako Iitani; Kenji Imai; Takafumi Ushida; Sho Tano; Kosuke Yoshida; Akira Yokoi; Rika Miki; Hiroyuki Kidokoro; Yoshiaki Sato; Yuichiro Hara; Tomoo Ogi; et al. (Communications Biology)
Abstract Histological chorioamnionitis (HCA) is a form of maternal immune activation (MIA) linked to an increased risk of neurodevelopmental disorders in offspring. Our previous study identified neurodevelopmental impairments in an MIA mouse model mimicking HCA. Thus, this study investigated the role of CD11c+ microglia, key contributors to myelination through IGF-1 production, in this pathology. In the mouse model, the CD11c+ microglial population was significantly lower in the MIA group than in the control group on postnatal day 3 (PN3d). Furthermore, myelination-related protein levels significantly decreased in the MIA group at PN8d. In humans, preterm infants with HCA exhibited higher IL-6 and IL-17A cord-serum levels and lower IGF-1 levels than those without HCA, followed by a higher incidence of delayed myelination on magnetic resonance imaging at the term-equivalent age. In silico analysis revealed that the transient induction of CD11c+ microglia during early development occurred similarly in mice and humans. Notably, a lack of high CD11c+ microglial population has been observed in children with neurodevelopmental disorders. This study reports impaired induction of CD11c+ microglia during postnatal development in a mouse model of MIA associated with delayed myelination. Our findings may inform strategies for improving outcomes in infants with HCA.